Adsorption behaviour and mechanism of the PFOS substitute OBS (sodium p-perfluorous nonenoxybenzene sulfonate) on activated carbon. Issue 9 (11th September 2019) - Wang, Wei; Mi, Xin; Shi, Huilan; Zhang, Xue; Zhou, Ziming; Li, Chunli; Zhu, Donghai
Abstract : Perfluorooctane sulfonate (PFOS) was listed as a persistent organic pollutant by the Stockholm Convention. As a typical alternative to PFOS, sodium p -perfluorous nonenoxybenzene sulfonate (OBS) has recently been detected in the aquatic environment which has caused great concern. For the first time, the adsorption behaviour and mechanism of OBS on activated carbon (AC) with different physical and chemical properties were investigated. Decreasing the particle size of AC can accelerate its adsorption for OBS, while AC with too small particle size was not conducive to its adsorption capacity due to the destruction of its pore structure during the mechanical crushing process. Intra-particle diffusion had a lesser effect on the adsorption rate of AC with smaller particle size, higher hydrophilicity and larger pore size. Reactivation of AC by KOH can greatly enlarge their pore size and surface area, greatly increasing their adsorption capacities. The adsorption capacity of two kinds of R-GAC exceeded 0.35 mmol g −1, significantly higher than that of other ACs. However, increasing the hydrophilicity of AC would decrease their adsorption capacities. Further investigation indicated that a larger pore size and smaller particle size can greatly enhance the adsorptive removal of OBS on AC in systems with other coexisting PFASs and organic matter due to the reduction of the pore-blocking effect. The spent AC can be successfully regenerated by methanol, and it can be partly regenerated by hot water and NaOH solution. The percentage of regeneration for the spent AC was 70.4% with 90°C water temperature and up to 95% when 5% NaOH was added into the regeneration solution. These findings are very important for developing efficient adsorbents for the removal of these newly emerging PFASs from wastewater and understanding their interfacial behaviour.